Exploring the Role of Barangay CCTV Operations in Crime Prevention and Emergency Response: A Qualitative Study in Mandaluyong City - Marahay, Jemuel (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored the role of barangay Closed-Circuit Television (CCTV) operations in crime prevention and emergency response in selected barangays in Mandaluyong City. Anchored on Rational Choice Theory, Routine Activity Theory, and Systems Theory, the study examined how CCTV systems influence offender behavior, strengthen guardianship, and support coordination among barangay officials, CCTV operators, law enforcement agencies, emergency responders, and community members. The study employed a qualitative research design using a phenomenological approach. Ten participants, consisting of barangay officials, CCTV operators, barangay tanods, and residents, were selected through purposive sampling. Data were gathered using a validated semi-structured interview guide and analyzed through Colaizzi’s phenomenological method. Findings revealed that barangay CCTV systems improved monitoring, situational awareness, perceived safety, investigation, evidence gathering, accountability, transparency, and emergency response coordination. However, their effectiveness was limited by low-resolution cameras, unclear nighttime footage, unstable connectivity, power interruptions, absence of backup systems, limited personnel, insufficient training, funding constraints, weak coordination, privacy concerns, and unclear access protocols. The study concludes that CCTV systems are most effective when supported by reliable infrastructure, active monitoring, trained personnel, adequate funding, clear operational procedures, transparent governance, community trust, and integration with crime mapping and policing strategies. The study aligns with SDG 9, SDG 11, SDG 16, and SDG 17 by supporting technological infrastructure, safer communities, accountable institutions, and inter-agency partnerships. Its sustainability impact lies in strengthening public safety, technology governance, community trust, policy development, and sustainable barangay-level security operations.